(untitled) (Conference Zone, 2022)
The article scientifically analyzes one of the most urgent problems of our time, the problem of education and career guidance of young people. The period of professional adaptation usually goes through three specific stages, each of which is characterized by important aspects of the teacher’s professional education. The first stage of adaptation is called familiarization and ends with his awareness of his new role in the environment. The second stage of professional adaptation is called training, and the acquisition of a specialty requires an in-depth study of knowledge (skills) in the specialty, the basics of general technical and humanitarian sciences. The third stage of professional adaptation is considered the main one and is characterized by the integration of a young specialist into the environment of the institution.